Delivering the Undeliverable: Teaching English in a University Today (International Journal of Food and Nutritional Sciences, 2022)
In UK universities, English has seen a steep fall in admissions, in the context of a general decline in humanities enrolments and changes to the school curriculum which have turned students away from the subject. This article explores what teaching English in a university means in these difficult times. It asks: what actually happens in an English class? What do students learn? And why is it so hard to make the case for English, to find a form of words in today’s educational vocabulary that will convince sceptics of its value? The subject’s declining status is part of a more general sense that technological change and the free market have answered all the key questions about what skills we need to learn and how we should live our lives. We frame the delivery of teaching in terms suggested by technology and the market – as a frictionless process with a predictable and measurable outcome. This does not sit well with the untidily human, stochastic, accretive nature of humanities teaching. And yet the skills of close reading cultivated in literary study can teach students to plot a course through contemporary life. They can help them to navigate a digitized, online, data-driven world whose meanings and values are filtered through unexamined words and unacknowledged stories.